The Role of Microsoft Excel as a Financial Statement Analysis Tool in Supporting a Company’s Financial Performance - Fatmawati Fatmawati; Masyhuri Masyhuri (Journal of Management, Entrepreneurship, and Tourism, 2026)
This study examines the role of Microsoft Excel as a financial statement analysis tool in supporting corporate financial performance through a qualitative non empirical literature review approach. The analysis integrates perspectives from accounting information systems, financial reporting quality, internal control, corporate governance, and digital financial transformation. The findings indicate that Microsoft Excel continues to provide substantial value in organizing, processing, and interpreting financial information, particularly in environments requiring accessible and adaptable analytical tools. At the same time, the literature identifies significant limitations associated with spreadsheet based analysis, including human error, formula inaccuracies, weak auditability, data inconsistency, and governance related vulnerabilities that may reduce the reliability of financial reporting. The study further reveals that the emergence of artificial intelligence, business intelligence platforms, enterprise resource planning systems, and XBRL based reporting technologies has transformed the financial analytics landscape without eliminating the relevance of Excel. Its strategic contribution increasingly depends on integration with broader digital ecosystems. Financial performance benefits arise indirectly through improved information quality, stronger governance practices, enhanced reporting credibility, and more effective managerial decision making processes.